2021
DOI: 10.3390/rs13163248
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Aerosol and Cloud on the Solar Energy Potential over the Central Gangetic Himalayan Region

Abstract: We examine the impact of atmospheric aerosols and clouds on the surface solar radiation and solar energy at Nainital, a high-altitude remote location in the central Gangetic Himalayan region (CGHR). For this purpose, we exploited the synergy of remote-sensed data in terms of ground-based AERONET Sun Photometer and satellite observations from the MODerate Resolution Imaging Spectroradiometer (MODIS) and the Meteosat Second Generation (MSG), with radiative transfer model (RTM) simulations and 1 day forecasts fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 75 publications
1
15
0
Order By: Relevance
“…The variation was found to be from 0 to 25% for AMF and 55% for CMF. It can be observed that the AMF values were dominated by values ranging between 0.5 to 0.8 [36], which indicate heavy aerosol content during these months. The frequency of occurrence of AMF was highest in the range of 0.5 to 0.8, and was within 5% for other values.…”
Section: Solar Radiation Effectsmentioning
confidence: 94%
See 4 more Smart Citations
“…The variation was found to be from 0 to 25% for AMF and 55% for CMF. It can be observed that the AMF values were dominated by values ranging between 0.5 to 0.8 [36], which indicate heavy aerosol content during these months. The frequency of occurrence of AMF was highest in the range of 0.5 to 0.8, and was within 5% for other values.…”
Section: Solar Radiation Effectsmentioning
confidence: 94%
“…The spatial resolution of the aerosol optical depth at a 550 nm forecast used in the present study was 0.4 • × 0.4 • (spatial resolution of the CAMS forecasts), whereas the temporal resolution of CAMS reanalysis is 3 hourly. The use of the CAMS AOD and other details are described in several earlier papers, and are hence not repeated here [36,42,[46][47][48][49].…”
Section: Aerosol Modellingmentioning
confidence: 99%
See 3 more Smart Citations